2000
DOI: 10.1038/sj.bmt.1702377
|View full text |Cite
|
Sign up to set email alerts
|

The effect of busulphan on the pharmacokinetics of cyclophosphamide and its 4-hydroxy metabolite: time interval influence on therapeutic efficacy and therapy-related toxicity

Abstract: Summary:Busulphan and cyclophosphamide (Bu/CP) are widely used in preparative regimens for bone marrow transplantation. Many studies have shown a wide variation in busulphan pharmacokinetics. Moreover, higher rates of liver toxicity were reported in Bu/CP protocols than in a total body irradiation (TBI)-containing regimen. In the present paper we investigated the effect of the time interval between the last dose of busulphan and the first dose of cyclophosphamide on the pharmacokinetics of CP and its cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 35 publications
5
99
2
1
Order By: Relevance
“…Compared with previous reports from patients receiving BU/CYconditioning regimen, 17,19,20 there was significantly decreased formation of HCY and increased AUC of CY in this study resulting in lower AUC HCY/CY ratio (Table 4). This difference in PK parameters could be age related because all the previous studies were from adult patients, whereas patients in this study are all under 15 years.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Compared with previous reports from patients receiving BU/CYconditioning regimen, 17,19,20 there was significantly decreased formation of HCY and increased AUC of CY in this study resulting in lower AUC HCY/CY ratio (Table 4). This difference in PK parameters could be age related because all the previous studies were from adult patients, whereas patients in this study are all under 15 years.…”
Section: Discussioncontrasting
confidence: 51%
“…As it has been shown that the PK of HCY is formation-rate limited, a better measure of exposure to this metabolite was suggested to be the ratio of AUC-HCY/ AUC-CY. 20 This is henceforth called AUC 4HCY/CY ratio in this article.…”
Section: Cy and Hcy Pk Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of hepatic glutathione-S-transferase by acrolein (Scott and Kirsch, 1988), as well as direct glutathione depletion (DeLeve, 1996), may cause acrolein accumulation in the liver after administration of high doses of cyclophosphamide. High-dose busulphan may also cause a depletion of glutathione and glutathione-S-transferase levels (Hassan et al, 2000). Therefore, the combination cyclophosphamide/busulphan, regularly used in the bone marrow transplantation setting, is often complicated by hepatic toxicity (Nevill et al, 1991;McDonald et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Applying BU before CY enhances hepatic conversion to the active drug and increases toxicity. 24 Therefore, the application of CY should be delayed for at least 24 h after BU.…”
Section: Discussionmentioning
confidence: 99%